2021
DOI: 10.20315/asetl.125.3
|View full text |Cite
|
Sign up to set email alerts
|

Značilnosti opravljanja sečnje in spravila v zasebnih gozdovih v Sloveniji

Abstract: A survey conducted in 2019 covered 544 randomly selected forest owners. More than half of the forest owners own a forest estate ranging from 1 to 4.99 ha. For 62 % of respondents, the primary purpose of forest management is to harvest wood for their own needs. In 2015%2019, 71 % of respondents carried out felling and skidding in their forests. In total, approximately 50,000 m3 of wood was felled (24 m3 /ha or 141 m3 per holding). The largest volumes were felled by private owners with small forest holdings (up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…However, the results of the survey show that male private forest owners harvested somewhat more intensively during the period under consideration. Studies abroad also confirm that male forest owners harvest more than female forest owners (Kuuluvainen et al, 2014;Ščap et al, 2021).…”
Section: Harvesting Characteristics Of Surveyed Private Forest Ownersmentioning
confidence: 85%
“…However, the results of the survey show that male private forest owners harvested somewhat more intensively during the period under consideration. Studies abroad also confirm that male forest owners harvest more than female forest owners (Kuuluvainen et al, 2014;Ščap et al, 2021).…”
Section: Harvesting Characteristics Of Surveyed Private Forest Ownersmentioning
confidence: 85%
“…However, the results of the survey show that male private forest owners harvested somewhat more intensively during the period under consideration. Studies abroad also confirm that male forest owners harvest more than female forest owners (Kuuluvainen et al, 2014;Ščap et al, 2021).…”
Section: Harvesting Characteristics Of Surveyed Private Forest Ownersmentioning
confidence: 85%
“…In some cases, the percentage of passive forest owners can be discouragingly high. Pezdevšek Malovrh et al [111] suggest that the segment of passive forest owners is significant in Slovenia, reaching levels as high as over 30%, while Ščap et al [116] report that almost a quarter (23%) have no intentions for regular logging. Recently, Matilainen and Lahdesmaki [114] revealed that the share of passive forest owners in Finland is even larger, with 35% identified as totally passive, while an additional 12% and 16% exhibit passiveness specifically in terms of timber sales and forest management, respectively.…”
Section: Higher Financial Compensation May Not Always Be Preferredmentioning
confidence: 99%